Transformasi digital dan dampaknya pada masyarakat dan bisnis - Abdillah, Nur Muhammad (Maliki Interdisciplinary Journal, 2024)
Digital transformation is the process of integrating digital technology into all aspects of society and business. This has a significant impact on various aspects, including the economy, society, and culture. This journal discusses digital transformation and its impact on society and business. This journal will discuss how digital transformation is changing the way people live, work, and interact. This journal will also discuss how digital transformation is changing the way businesses operate and compete.